Does Access to Microfinance Improve Farm Production? Evidence from Rice Farmers in San Francisco, Agusan del Sur, Philippines - Sarmiento, Jon Marx P; Ellson, Adela G; Traje, Adonis M; Manzano, Gianne Francis Alfred E; Comidoy, Sherleen M (Asian Journal of Agriculture and Rural Development, 2013)
Poverty level remains high (36.7%) in agricultural areas in the Philippines. The second poorest province in the Philippines is Agusan del Sur with incidence reaching as high as 51.2%. One of the approaches to alleviate poverty is to provide access to capital through microfinance. This study draws conclusion on the link between access to microfinance and farm production taking the municipality of San Francisco in Agusan del Sur as a case. A total of 95 rice farmers were interviewed. Data revealed that microfinance client farmers were producing 27% more than non-client farmers. The production data were fitted using five production functions namely; (1) Neoclassical, (2) Neoclassical with interaction, (3) Cobb-Douglas, (4) Transcendental and (5) Transcendental with interaction. Using ordinary least squares method, Neoclassical function best fit the data with access to microfinance significantly improving farm production by 23%. Output was most responsive to land (0.60 elasticity (E)), followed by fertilizer (0.18 E), labor (0.14 E), herbicide (0.12 E), seed (0.02 E) and pesticide use (0.00 E). Irrigated farms were 23% more productive than non-irrigated farms. Despite the positive impact of access to microfinance, only 34% of the farmers had availed agricultural microfinance loan from formal institutions while only 18% took advantage during the 2nd season of 2010 rice production.